Pengaruh Fraksi Volume Terhadap Sifat Tarik Komposit Diperkuat Serat Tebu Dengan Matrik Poliester - Harita, Revival Praise; Dharta, Yuli; Napitupulu, Robert (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Indonesia, which has a tropical climate, is one of the largest producers of cane sugar in the world. Therefore, waste from the sugar cane production process has the potential to be an alternative material for composite material fillers, as it is easily available and environmentally friendly. Along with industrial development, innovation in composite materials is also advancing, especially thanks to the abundance of abundant and renewable resources. This research aims to develop composites from sugarcane fibers with polyester resin as the binder matrix. The prepared fibers were then soaked in 5% NaOH solution with volume fraction variations of 10%, 15%, and 20%, and arranged randomly. The composite manufacturing process was carried out using the hand lay-up method. Tests carried out on the specimens were tensile tests with ASTM D638 standards, which were carried out at the Bangka Belitung State Manufacturing Polytechnic. The results showed that the highest tensile strength was recorded at a volume fraction of 20% sugarcane fiber after soaking for 4 hours with NaOH, which was 27.94 MPa. In contrast, the lowest tensile strength was obtained at a volume fraction of 10% sugarcane fiber with 2 hours of NaOH immersion, which reached 24.25 MPa. This finding is consistent with previous research which shows that fiber volume fraction and immersion time with NaOH play an important role in increasing the strength of fiber structures in composites.